The Renin–Angiotensin–Aldosterone System and Coronavirus Disease 2019 - Eliecer Coto; Pablo Avanzas; Juan Gómez (European Cardiology Review, 2021)
The renin–aldosterone–angiotensin system (RAAS) plays an important role in the pathogenesis of coronavirus disease 2019 (COVID-19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Angiotensin-converting enzyme 2 (ACE2) is the cellular receptor for SARS-CoV-2 and the host’s expression of this membrane-bound protein could affect susceptibility to infection. The RAAS is an important regulator of cardiovascular physiology and ACE2 has an essential role. People with hypertension and other traits have shown to have an imbalance in ACE/ACE2 levels and reduced levels of ACE2 could enhance the risk of adverse outcome in patients with COVID-19. It has been hypothesised that the RAAS may mediate the interplay between cardiovascular disease and COVID-19 severity. Evidence shows that antihypertensive drugs that target the RAAS have no significant effect on the risk of infection and disease outcome. Variations in RAAS genes have been associated with the risk of developing hypertension and cardiovascular disease and could partly explain the heterogenous response to SARS-CoV-2 infection. This article explores the interplay between the RAAS and COVID-19, with emphasis on the possible relationship between genetic variations and disease severity.